Global burden of disease from high-sodium diets, 1990–2021: analysis of GBD 2021 data - Nie, Yanwu; Wang, Naibo; Huang, Mingzhu; Li, Yuanzhi; Lu, Yuanan; Li, Hui; Wu, Lei (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to assess the global, regional, and national burden of disease attributable to high-sodium diets from 1990 to 2021.MethodsData on the global high-sodium diet-related disease burden were obtained from the Global Burden of Disease 2021 (GBD2021). A Bayesian age-period-cohort model (BAPC) was used to project trends from 2022 to 2040.ResultsBetween 1990 and 2021, both the age-standardized death rate (ASDR) and age-standardized disability-adjusted life years rate (ASYR) attributable to high-sodium diets declined. The burden varied across Social Development Index (SDI) levels, regions, and countries, with Central Europe, East Asia, and Southeast Asia experiencing the highest burden. At the national level across 204 countries, the Republic of Bulgaria recorded the highest ASDR and ASYR, while the Islamic Republic of Pakistan experienced the most rapid increases in both ASDR and ASYR. Additionally, the ASDR and ASYR increased with age and were consistently higher in men than in women. The GBD2021 reported 8 diseases attributed to high-sodium diets, arranged in descending order of disease burden as follows: stroke, Ischemic heart disease, Hypertensive heart disease, Stomach cancer, Chronic kidney disease, Atrial fibrillation and flutter, Aortic aneurysm, Lower extremity peripheral arterial disease. The BAPC prediction results showed that the ASDR and ASYR of high-sodium diets would decrease by 23.28 and 19.46%, respectively, from 2022 to 2040.ConclusionsThe global disease burden due to high-sodium diets has decreased over the past three decades, though disparities remain. Targeted investigations are urgently needed, particularly in high-burden regions, to further reduce the health impacts of excessive sodium intake.